Effects of thermal, alkaline and ultrasonic treatments on scleroglucan stability and flow behavior - Viñarta, Silvana Carolina (2013)
Aqueous solutions (0.2%, w/v) of scleroglucans from Sclerotium rolfsii ATCC 201126 from different cultivation time or purification protocol (EPS I, EPS II, EPSi) as well as a commercial scleroglucan (LSCL) exhibited different sensitivity against thermal (65, 95 and 150 ◦C), ultrasonic (1, 5 and 10 min; 20% amplitude) or alkaline (0.01-0.2 N NaOH) treatments. Scleroglucan triple helix usually showed signs of denaturation at 150 ◦C or with 0.2 NaOH with a pronounced decrease in apparent viscosity and loss of pseudoplastic behavior. Differences in sensitivity could be noted depending on the scleroglucan sample, which may be likely related to polysaccharide conformational features, and these latter to production and/or downstream processing conditions. Transmission electronmicroscopy showed scleroglucan topologies in accordance with thermal and alkaline denaturation. Size exclusion chromatography of control scleroglucans revealed elution profiles compatible with macromolecular aggregates which tended to diminish or disappear as thermal, alkali or sonication treatments progressed. Scleroglucan granule dissolution process took ∼8-14 s, according to DIC light microscopy, and showed to be facilitated by addition of NaOH.